The Effect of Transformational Leadership on Psychological Well-Being and Job Performance in Higher Education Institution - Medina, Rizka; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Ekonomis: Journal of Economics and Business, 2024)
This research aims to analyze the influence of transformational leadership on psychological well-being with job performance through job satisfaction as a mediating variable. The data collection method used was a survey using Google Form. This research uses SEM (structural equation model) analysis, by first analyzing the data to test validity, reliability and hypothesis testing with the help of the AMOS program with a sample of 130 educational staff from various work units. The research results show that (1) transformational leadership has a positive effect on job satisfaction; (2) transformational leadership has no influence on psychological well-being; (3) transformational leadership has a positive effect on job performance; (4) transformational leadership has a positive effect on psychological well-being through job satisfaction; (5) transformational leadership has a positive effect on job performance through job satisfaction; (6) job satisfaction has a positive effect on psychological well-being; and (7) job satisfaction has no influence on job performance.